EFEKTIFITAS PEMBELAJARAN MATEMATIKA HUMANISTIK BERBASIS KONSTRUKTIVISME BERBANTUAN E-LEARNING MATERI SEGI TIGA PADA KELAS 7 SMP N 2 LIMPUNG TAHUN AKADEMIK 2009/2010 - Muhammad Prayitno (LPPM Universitas Pekalongan, 2011)
This research is based on the use of ineffective learning models which haven’t based on the humanistic values and the lack of constructivism in compounding the students’ knowledge so that the students’ achievement is disappointed and the negative view of the students in learning math. This is an experimental research, and the research question is that will the constructivism based humanistic mathematic by e- learning of the triangle course of the seventh grade be effective? The active skill process is as the independent variable and the learning achievement is as the dependant variable. The data is found out by learning achievement test and question sheets. The research method is descriptive, the analysis of the sample t test and regression. The influence test is by a simultaneous study to find out the learning achievement, the influence of activeness to the learning achievement and the difference between the control classes to the experiment class.The result of the research is that the learning is effective, signed by 3 indicators, they are; (1) the students’ achievement is up to the classical achievement 69,28 more than KKM 60, and the individual achievement is up to 75%, (2) the activeness of the students gives a positive influence to the students’ achievement; 33,8%, (3) the average of the experiment class is 69,28 better than the control class in average 63,67. Key words: the learning effectiveness, Humanistic, constructivism.